Determinants of corporate social responsibility practices: institutional pressure or strategic opportunity? - Lourenço, Maria Salvelina Marques; Sousa-Filho, José Milton (Revista de Administração da UFSM, 2020)
Institutional theory and strategic studies suggest the existence of a potential paradox in its foundations. Previous studies on institutional and strategic factors that determine Corporate Social Responsibility (CSR) practices do not address this paradox. The purpose of this research was to understand how potentially divergent factors explain the same phenomenon: CSR involvement. For this purpose, a qualitative research was carried out in a large-scale industry from the Brazilian footwear sector. Interviews and company documents provided the data, which were analyzed through content analysis. The results revealed that institutional and strategic factors positively influence CSR practices in a complementary relationship. Therefore, it is concluded that there is no incompatibility between the institutional and strategic determinants of CSR. Instead, there is a complementary relationship. Thus, this research is expected to contribute in deepening the understanding of the determinants of CSR. It is also expected that business managers will view institutional pressures as strategic opportunities.